Integrasi Ornamen Batik dalam Arsitektur dan Penataan Ruang Islam sebagai Penguat Identitas Budaya Indonesia - Habib Auliya Rahman (Journal of Engineering and Applied Technology, 2025)
This study examines the integration of batik ornamentation into Islamic architectural and spatial design as a culturally grounded strategy to reinforce Indonesia’s national identity. Batik, as a symbolic visual language deeply rooted in Indonesian heritage, possesses philosophical depth that aligns with the spiritual and aesthetic principles of Islamic art. The research synthesizes literature on architectural identity, symbolic ornamentation, and cultural adaptation to trace how batik motifs can be meaningfully incorporated into façades, interiors, and urban religious environments. Findings reveal that successful integration requires careful selection of motifs, technological adaptation through digital processing, and collaborative interpretation between designers, scholars, and religious authorities to maintain symbolic coherence. Hybrid design approaches enable traditional motifs to coexist with contemporary Islamic architectural expressions without losing their cultural essence. This paper argues that integrating batik into Islamic architecture not only enriches visual harmony but also strengthens collective cultural consciousness among communities. Ultimately, batik-based architectural design presents a viable model for developing culturally resonant, spiritually grounded, and contextually relevant Islamic spaces in Indonesia.